Comparative analysis of flavonoids in white and red table grape cultivars during ripening by widely targeted metabolome and transcript levels. Issue 4 (22nd March 2022) - Xia, Hui; Zhang, Xuefeng; Shen, Yanqiu; Guo, Yuqi; Wang, Tong; Wang, Jin; Lin, Lijin; Deng, Honghong; Deng, Qunxian; Xu, Kunfu; Lv, Xiulan; Liang, Dong
Abstract: The flavonoid metabolites were compared between red 'Summer Black' (SB) and white 'Shine Muscat' (SM) table grapes during fruit development based on widely targeted metabolome. A total of 134 flavonoids were identified in two cultivars, including 37 flavones, 33 flavonols, and 11 anthocyanidins, and so on. From young to veraison, the composition and the content of most flavonoids were decreasing in both cultivars but increased at maturation in SB. In general, SB has higher flavonoid compositions and content than SM during the whole fruit development, especially the content of anthocyanin after veraison. While the SM had higher content of flavonols such as quercetin, kaempferol and their derivatives. The expression of anthocyanin‐related genes such as UFGT, OMT, GST, MATE, MYBA1, and MYBA2 was remarkably higher in SB than those in SM, which may attribute to higher anthocyanin content, while the higher expression of F3H and FLS resulted higher level of flavonols in SM. These results improve our understanding of flavonoid profiles and molecular mechanism in table grape cultivars.